Pengaruh komposisi penambahan serat polypropylene terhadap kuat tekan dan kuat lentur self compacting mortar (SCM) - Suma, Damas Novalda; Noorhidana, Vera Agustriana; sebayang, surya; Isneini, Mohd. (Universitas Lampung, 2023)
AbstractSelf compacting mortar is a mortar which is able to flow under its own weight and completely fill the formwork without the need for external compaction, while maintaining its homogeneity. This study aims to determine the effect of variations in the addition of polypropylene fiber to the compressive strength and flexural strength of self compacting mortar (SCM), as well as to determine the optimum variation of the addition of polypropylene fiber in mixed mortar. In this study, the test specimens were made with a water-cement factor of 0.4 and the ratio between cement and fine aggregate was 1:2.5 and the addition of 2% superplasticizer by weight of cement and the addition of polypropylene fibers with variations of 0%, 0.04%, 0.06%, 0.08%, 0.1% of the volume of the mortar test object. Tests were carried out on specimens aged 28 days. The results showed that the compressive strength of SCM experienced an optimum increase in the addition of 0.04% polypropylene fiber which was 34.81 MPa with an increase percentage of 14.07% of mortar without fiber, while the flexural strength of SCM increased with increasing variations of polypropylene fiber until the increase The optimum variation occurred at 0.1% polypropylene fiber, namely 11.72 MPa with a percentage increase of 26.05% from mortar without fiber. Key words : polypropylene fiber, superplasticizer, compressive strength, flexural strength.